MicroRNAs and their potential therapeutic applications in neural tissue engineering - Nguyen, Lan Huong (2015)
The inherent poor regeneration capacity of nerve tissues, especially in the central nervous system, poses a grand challenge for neural tissue engineering. After injuries, the local microenvironment often contains potent inhibitory molecules and glial scars, which do not actively support axonal regrowth. MicroRNAs can direct fate of neural cells and are tightly controlled during nerve development. Thus, RNA interference using microRNAs is a promising method to enhance nerve regeneration. Although the physiological roles of microRNA expression levels in various cellular activities or disease conditions have been extensively investigated, the translational use of these understanding for neural tissue engineering remains limited. This review aims to highlight essential microRNAs that participate in cellular behaviors within the adult nervous system and their potential therapeutic applications. In addition, possible delivery methods are also suggested for effective gene silencing in neural tissue engineering.